Effect of the use of Chia (Salvia Hispanica L.) seeds on antioxidant status and anthropometric parameters in obese, type 2 diabetics and/or hypertensive patients (Research, Society and Development, 2022)
Background and aims: Chia seeds have been explored owing to its dense concentrations of antioxidant and anti-inflammatory compounds, as well as recognized benefit on anthropometric measures. This study evaluated the potential effect of Chia intake on plasma antioxidant status and anthropometric parameters in individuals with chronic diseases. Methods: Fifty-nine participants were selected, including patients with Type 2 Diabetes Mellitus (T2DM) and/or hypertension (SAH) and/or obesity (group A, n=34) and healthy volunteers (group B, n=25). Plasma antioxidant status was determined by the MTT (tetrazolium salt) reduction test and weight (W), abdominal circumference (AC), waist circumference (WC) and body mass index (BMI), that were determined before (T0) and after 6 months (T6) of ingestion of 20 g/day of Chia seeds. Results: After Chia seeds consumption, the plasma antioxidant potential increased in both group A and group B (p < 0.0001). It was also observed a reduction in W, AC, WC and BMI in both groups, with all p-values being less than 0.05. High content of antioxidant compounds may explain these effects and polysaccharide gel formation in the digestive tract, which gives satiety and consequently provides a reduction in anthropometric measurements. Conclusion: In the field of nutrition, the chia seed can be a potential alternative to increase antioxidant status and reduce anthropometric measurements, improving the health status of patients, especially those who suffer from chronic disease.